Biodegradation potential assessment by using autochthonous microorganisms from the sediments from Lac Mégantic (Quebec, Canada) contaminated with light residual oil. (January 2020) - Yang, Zeyu; Hollebone, Bruce P.; Shah, Keval; Yang, Chun; Brown, Carl E.; Dodard, Sabine; Sarrazin, Manon; Sunahara, Geoffrey
Abstract: In July 2013, a fatal train derailment led to an explosion and fire in the town of Lac-Mégantic (LM), Quebec, and the crude oil contamination of regional surface water, soil, and sediment in the adjacent Lake Mégantic. This study investigated the degradation potential of the spilled crude oil by using the sediments from the incident site as the source of microorganisms. Two light crude oils (LM source oil and Alberta Sweet Mixed Blend (ASMB)) were tested at 22 °C for 4 weeks and 4 °C for 8 weeks, respectively. The post-incubation biological and chemical information of the samples were analysed. There was no marked difference in degradation efficacy and biological activities for both the LM and ASMB oils, although the biodegradation potential differed between the two incubations. Higher temperature favoured the growth of microorganisms, thus for the degradation of all petroleum hydrocarbons, except for some conservative biomarkers. The degradation of both oils followed the order of resolved components > total saturated hydrocarbons (TSH) > unresolved complex mixture (UCM) >total aromatic hydrocarbons (TAH). Normal alkanes were generally degraded more significantly than branched ones, and polycyclic aromatic hydrocarbons (PAHs). Degradation of polycyclic aromatic hydrocarbons (PAHs) and their alkylated congeners (APAHs) for both incubations generally decreased as the number of aromatic rings, and the degree of alkylation increased. This study showed that the LM sediments can biodegrade the petroleum hydrocarbons efficaciously if appropriate ambient temperatures are generated to favour the growth of autochthonous microorganisms. Highlights: Biodegradation of petroleum hydrocarbons depends on their chemical structure. Higher temperatures favoured the biodegradation of petroleum hydrocarbons. Native microorganisms from LM sediments can biodegrade petroleum hydrocarbons.